Reducing antigenicity of bovine whey proteins by Kluyveromyces marxianus fermentation combined with ultrasound treatment. (1st May 2020) - Zhao, Wenjun; Shu, Qing; He, Guoqing; Qihe, Chen
Highlights: The structure change of bovine whey protein by ultrasonic treatment was studied. The cultivation conditions were optimized for reducing whey protein antigenicity. The fermentation reduction of alpha-lactalbumin and beta-lactoglobulin antigenicity was obtained. Abstract: This work investigated the reduction of bovine whey proteins antigenicity by ultrasonic pretreatment and microbial fermentation. Firstly, bovine whey proteins was pretreated by ultrasonic techniques, and its secondary structure was detected by circular dichroism. The pretreated whey proteins was used as the fermentation substrate by Kluyveromyces marxianus for microbial transformation. The single factor design and Box-Behnken Design (BBD) were carried out with the aim to optimize culture temperature, initial pH, inoculum volume and rotation speed. After optimization process, culture temperature, initial pH, inoculum volume and rotation speed were determined. Under culture temperature 35 °C, pH 7.25, inoculum level 10% and shaking speed 150 rpm, the α-LA and β-LG antigenicity in bovine whey proteins were reduced by 29% and 53%, respectively. The findings showed that combined with microbial fermentation for hydrolysis of whey proteins, ultrasonic pretreatment can be used in order to produce hypoallergenic bovine whey proteins.